Use of Spiritually Framed Information Messages to Improve Cancer Screening - Baransel, Esra Sabanci; Barut, Sumeyye (Elsevier Science Inc, 2023)
This study aimed to determine the effect of spiritually framed information messages on breast and cervical cancer screening tests participation plans and self-efficacy levels in Turkish Muslim women. This study was conducted as a randomized controlled trial with 3 treatment groups. Each group consisted of 335 women. Study findings suggest that spiritually framed information messages on breast and cervical cancer screening tests can elicit positive thoughts on cancer self-efficacy and participation in breast and cervical cancer early screening tests.(c) 2023 Elsevier Inc. All rights reserved.
Keywords: breast cancer; cervix cancer; message; spiritually; self-efficacy